Slightly irregular - Pollero, Rhonda (Gallery Books, 2012)
"The fourth novel in the F.A.T. series finds Finley Tanner facing two impossible tasks: track down a missing lawyer from her firm, and find a date for her sister's wedding. Finley may have bitten off more than she can chew when she discovers that the lawyer is not who she claims to be--and may be implicated in the unsolved murder of a pageant queen. On top of that, Finley's taking her boss, Tony, to her sister's wedding...even though she still has feelings for bad-boy cop Liam. Does a paralegal with a talent for crime solving and designer bargain-hunting ever get to put her feet up and search eBay? Not when West Palm Beach is this hot"--